2020
DOI: 10.1007/s00213-020-05481-4
|View full text |Cite
|
Sign up to set email alerts
|

Decreased sensitivity in adolescent versus adult rats to the antidepressant-like effects of cannabidiol

Abstract: Rationale Cannabidiol is a non-psychoactive phytocannabinoid with great therapeutic potential in diverse psychiatric disorders; however, its antidepressant potential has been mainly ascertained in adult rats. Objectives To compare the antidepressant-like response induced by cannabidiol in adolescent and adult rats and the possible parallel modulation of hippocampal neurogenesis. Methods Male Sprague-Dawley rats were repeatedly treated with cannabidiol (3, 10, and 30 mg/kg) or vehicle (1 mL/kg) during adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 58 publications
6
26
1
Order By: Relevance
“…The administration of CBD displayed antidepressant-like effects at different doses in adolescents and adult male Sprague-Dawley rats [122]. The long-lasting effects of CBD were different: 2 days for adolescent and 21 days for adult rats.…”
Section: Results From Animal Studiesmentioning
confidence: 94%
“…The administration of CBD displayed antidepressant-like effects at different doses in adolescents and adult male Sprague-Dawley rats [122]. The long-lasting effects of CBD were different: 2 days for adolescent and 21 days for adult rats.…”
Section: Results From Animal Studiesmentioning
confidence: 94%
“…The second part of the study evaluated the impact of adolescent cocaine exposure on affective-like behavior when the combination of several risk factors was present (i.e., female rats and early-life stress). The goal of the study was to ascertain the impact of cocaine exposure only in female rats (e.g., Rowson et al 2018 ) exposed to early-life stress, as opposed to perform a direct comparison with male rats and/or with non-stressed control rats, since prior similar studies have been done exclusively in male rats (Bis-Humbert et al 2020 ; 2021a , 2021b ), and we tackled the comparison with non-stressed controls in the first part of this study. At the behavioral level, the results showed that cocaine exposure did not alter affective-like behavior during adolescence, since no changes were observed in the forced swim, novelty-suppressed feeding, or sucrose preference tests.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were screened in several behavioral tests performed consecutively across time to measure affective-like responses (Gururajan et al 2019 ) and as done in several prior studies (García-Cabrerizo and García-Fuster 2019 ; Jiménez-Romero et al 2020 ; Bis-Humbert et al 2020 ; 2021a , 2021b ): forced swim, open field, novelty-suppressed feeding, and sucrose preference (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical evidence indicates that CBD may reduce depressive-like behaviours, via several potential mechanisms of action (see [ 9 ]). Several animal studies have shown that CBD can reduce autonomic indices of stress and depression- and anxiety-like behaviours [ 128 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ]. In terms of human studies, there are some published case studies which indicate that CBD reduced depressive symptoms [ 158 , 159 ] but no RCTs published in this area yet.…”
Section: Evidence Of Efficacy Of Cbd In Management Of Cancer and Canc...mentioning
confidence: 99%